Prevalence of Absence of Function of the Flexor Digitorum Superficialis Muscle Tendons in the Fourth and Fifth Fingers of the Hand in the Brazilian Population - Oliveira, Bruno Macêdo (Sociedade Brasileira de Ortopedia e Traumatologia. Published by Thieme Revinter Publicações Ltda, 2020)

(untitled) (Rev Bras Ortop (Sao Paulo))
Objectives  To evaluate the prevalence of absence of flexor digitorum superficialis muscle tendons function of the fourth and fifth fingers of the hand in the Brazilian population Methods  Prospective study performed at the orthopedics and traumatology department of a university hospital. The study was conducted from October 2017 to April 2018. The sample consisted of volunteers with no history of upper limb trauma, surgery or any other condition. This study included both male and female individuals over 18 years old. The flexor digitorum superficialis muscle tendons of the fourth and fifth fingers were evaluated through clinical tests by three independent examiners. The data were analyzed using GraphPad Prism 5.0 (GraphPad Software, San Diego, CA, USA). Results  A total of 2,016 hands from 1,008 volunteers were analyzed. The prevalence of absence of flexor digitorum superficialis muscle tendon function of the fourth finger was 0.56% at the right hand and 0.99% at the left hand. At the right hand, this prevalence was higher in females compared to males ( p  = 0.0328). No difference between genders was noted in the left hand ( p  = 0.7562). The prevalence of absence of flexor digitorum superficialis muscle tendon function of the fifth finger was 34.53% in the right hand and 30.06% in the left hand. This prevalence was higher in females compared to males, both at the right hand ( p  = 0.0001) and the left hand ( p  = 0.0003). Conclusion  Even though there are studies performed separately in different ethnic groups, there were no data in the literature regarding the prevalence of absence of flexor digitorum superficialis muscle tendons function of the fourth and fifth fingers of the hand in a multiethnic population such as the Brazilian one.